HUBUNGAN ANEMIA DAN USIA IBU DENGAN KEJADIAN ABORTUS DI RUMAH SAKIT BHAYANGKARA MAKASSAR - Yudiarsi Eppang; Nurhikmah (Stikes Graha Edukasi Makassar, 2021)
Objective: The objective of this study was to determine the relationship of anemia and maternal age with abortion in Bhayangkara Hospital Makassar 2019. Method: This study used Cross Sectional Study approach, population number 720 people and 87 samples, secondary data using check list, data processing with computerized program and data analysis with Chi-Square. Discussion: The abortion of one of the global health problems due to the large assessment of abortion problems in various countries faces many difficulties as a result of the illegal status of the abortus so that cases are rarely reported. However, without a clear and complete picture, abortion remains detectable as a serious public health problem. Results: The results of the study have anemia relationship with abortion and there is no relation between maternal age and abortion in Bhayangkara Makassar Hospital 2019. Conclusion: there is relation between maternal and maternal age with abortion incidence in hospital. Suggestion: The need to increase the knowledge to the community about the need for adequate nutrition fulfillment especially for pregnant women by utilizing life stalls and still taking drugs such as blood-boosting tablets so the risk of abortion can be minimized